The Profits Of Digitalization In Catering Bunda Li’s Business In Parepare - Darmawan Darmawan; Fitriyani Syukri; Fitriani Fitriani; Rosita Tri Wahyuna; Fitra Rahmadani (International Journal Of Community Service, 2025)
Digitalization has become one of the key strategies to enhance the competitiveness of micro, small, and medium enterprises (UMKM) in the modern economy. The community service activity themed Cuan ala Digitalisasi Usaha Catering Bunda Li’ aims to improve the business capacity through digitalization training and market access. This program is designed to introduce digital technology to catering business owners, such as the use of social media for promotion and online marketing strategies to expand market reach. The results of the activity show a positive impact on increased orders and customer numbers. By utilizing digital platforms, the catering business has successfully expanded its customer base. Additionally, the use of social media has helped improve business visibility and strengthen its brand image in a wider market. The business owner is now able to leverage digital technology to manage orders and promotions effectively.The digitalization and market access training program has proven to be effective in supporting the growth of Catering Bunda Li’. This initiative provides new opportunities for the business to develop sustainably in the digital era, while also increasing its contribution to the local economy.